P045 Effect of specialized 6-month physical-occupational intervention with subsequent 6-month follow-up period in patients with scleroderma – preliminary data. (March 2019) - Spiritovic, M; Smucrova, H; Oreska, S; Storkanova, H; Hermankova, B; Cesak, P; Rathouska, A; Ruzickova, O; Pavelka, K; Senolt, L; Vencovsky, J; Becvar, R; et al.
Abstract : Career situation of first and presenting author: Student for a master or a PhD. Introduction: Systemic sclerosis (SSc) is accompanied by stiffness and contraction of tissue, predominantly of the skin, caused by fibrosis and resulting in reduced quality of life. The aim of our study was to determine the effect of specialized physical-occupational intervention (POI) on hand/face function and strength, and quality of life of SSc patients. Objectives: The study included a total of 55 patients who fulfilled the EULAR/ACR criteria for SSc (2013) and had skin involvement leading to hand-function impairment and mouth handicap. 25 patients were recruited into the intervention group (IG) and 30 patients into the control group (CG). Both groups received educational material for home exercise, but only the IG underwent a 6 month intervention with a subsequent 6 month follow-up period. Methods: Patients were assessed by a physician and a physiotherapist blinded to intervention at months 0, 3, 6, and 12, and parameters evaluating hand/face and quality of life were recorded. Patients also filled out PRO (patient reported outcomes) questionnaires and provided blood for routine laboratory analysis and bio-banking. Data analysis was done between groups and within the group. Results: Compared to the observed statistically significant deterioration in the CG, we found a statistically significant improvement in the IG in objectively assessed function and strength of hand, distance between incisors and lips and functional ability (SHAQ). Only numerical improvements in the IG during the intervention compared to numerical deterioration in CG that did not reach statistical significance were observed in subjectively assessed hand function and mouth handicap, functional ability (HAQ) and in some domains of QoL (SF-36) and fatigue (FIS–in cognitive function). During the follow-up period, there was a significant deterioration or stagnation of the achieved positive results in the IG. Conclusions: Our specialized POI intervention led to a significant improvement in the observed parameters that was clinically significant in a substantial proportion of patients, and prevention of the expected worsening of hand/face function and strength and quality of life. Acknowledgements: Supported by AZV-16-33574A, SVV for FTVS UK 2019-260466, MHCR 023728. Disclosure of Interest: None declared